2004
DOI: 10.4269/ajtmh.2004.70.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Field Evaluation of the Mbita Trap, the Centers for Disease Control Light Trap, and the Human Landing Catch for Sampling of Malaria Vectors in Western Kenya

Abstract: The mosquito sampling efficiency of a new bed net trap (the Mbita trap) was compared with that of the Centers for Disease Control miniature light trap (hung adjacent to an occupied bed net) and the human landing catch in western Kenya. Overall, the Mbita trap caught 48.7 +/- 4.8% (mean +/- SEM) the number of Anopheles gambiae Giles sensu lato caught in the human landing catch and 27.4 +/- 8.2% of the number caught by the light trap. The corresponding figures for Anopheles funestus Giles were 74.6 +/- 1.3% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 17 publications
9
79
1
Order By: Relevance
“…The conversion factors for Arena Blanca and Riaba, although calculated from outdoor collections, are among the lowest reported in Africa [9-13,15-18] and approach the extremely low light trap collection efficiency (LTC:HLC = 0.02) found in urban Dar es Salaam, Tanzania [19]. The authors of that study suggested that the poor light trap performance was affected by the city lights and concluded that light traps are not appropriate for mosquito surveillance and monitoring the impact of mosquito control measures in Dar es Salaam [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conversion factors for Arena Blanca and Riaba, although calculated from outdoor collections, are among the lowest reported in Africa [9-13,15-18] and approach the extremely low light trap collection efficiency (LTC:HLC = 0.02) found in urban Dar es Salaam, Tanzania [19]. The authors of that study suggested that the poor light trap performance was affected by the city lights and concluded that light traps are not appropriate for mosquito surveillance and monitoring the impact of mosquito control measures in Dar es Salaam [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared various types of human-baited tent trap designs with LTCs and HLCs for estimating relative sampling efficiencies [15-19]. These studies also report widely varying 1:1 LTC:HLC relative sampling efficiencies; 0.02 in urban Dar es Salaam, Tanzania [19]; 0.33 in the Kilombero valley, Tanzania [17]; 0.56 in Ahero, western Kenya [16]; 1.3 also in Kilombero, Tanzania [18]; and 1.86 in Lwanda, western Kenya [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the EIR and the FOI has been measured, rediscovered and discussed several times 12,14,17,19,20 Bias in estimating the EIR could explain some of the pattern; several common methods of estimating the EIR are known to be biased relative to one another 39,40 . A bias in EIR could explain why the highest transmission efficiency in Saradidi was approximately half of that observed for experimental challenge to infectious mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquitoes possibly represent the most captured insect group in the world, and many methods to catch them have been devised (Figure 5), from which several can be selected that best answer the specific questions. For example, if the aim is to determine spatial variations in the EIR, then adult mosquitoes from light traps, tent or bednet traps (Mathenge et al 2002;2004), or landing or resting catches will suffice. If parasitaemias or human to mosquito transmission are of interest then mosquitoes with blood meals need to be collected.…”
Section: What Type Of Data and How Many?mentioning
confidence: 99%